Comparing the Predictors of Functional Outcomes After Arthroscopic Rotator Cuff Repair Modified Frailty Index, Clinical Frailty Scale, and Charlson Comorbidity Index. Issue 7 (2nd July 2021) - Moorthy, Vikaesh; Lee, Merrill; Ang, Benjamin Fu Hong; Chen, Jerry Yongqiang; Lie, Denny Tjiauw Tjoen
Background: The incidence of rotator cuff tears increases with age, and operative management is usually required in patients with persistent symptoms. Although several studies have analyzed the effect of age and comorbidities on outcomes after rotator cuff repair, no study has specifically examined the consequence of frailty. Purpose: To determine the best frailty/comorbidity index for predicting functional outcomes after arthroscopic rotator cuff repair. Study Design: Cohort study; Level of evidence, 3. Methods: The authors conducted a retrospective cohort study of 340 consecutive patients who underwent unilateral arthroscopic rotator cuff repair at a tertiary hospital between April 2016 and April 2018. All patients had undergone arthroscopic double-row rotator cuff repair with subacromial decompression by a single fellowship-trained shoulder surgeon. Patient frailty was measured using the Modified Frailty Index (MFI), Clinical Frailty Scale (CFS), and Charlson Comorbidity Index (CCI), calculated through retrospective chart review based on case notes made just before surgery; patient age and sex were also noted preoperatively. Functional outcomes using the Oxford Shoulder Score (OSS), Constant Shoulder Score (CSS), University of California Los Angeles (UCLA) Shoulder Score, and visual analog scale for pain were measured preoperatively and at 3, 6, 12, and 24 months postoperatively. Results: The MFI was a consistent significant predictor in all functional outcome scores up to 24 months postoperatively ( P < .05), unlike the CFS and CCI. Sex was also a significant predictor of postoperative OSS, CSS, and UCLA Shoulder Score, with male sex being associated with better functional outcomes. Patients with higher MFI scores had slower functional improvement postoperatively, but they eventually attained functional outcome scores comparable with those of their counterparts with lower MFI scores at 24 months postoperatively. Conclusion: The MFI was found to be a better tool for predicting postoperative function than was the CFS or CCI in patients undergoing arthroscopic rotator cuff repair. The study findings suggest that a multidimensional assessment of frailty (including both functional status and comorbidities) is important in determining functional outcomes after arthroscopic rotator cuff repair.